2021
DOI: 10.23736/s0022-4707.20.11205-2
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between isometric mid-thigh pull variables and athletic performance measures: empirical study of English professional soccer players and meta-analysis of extant literature

Abstract: BACKGROUND: There is currently limited evidence available to support the use of the isometric midthigh pull (IMTP) within professional soccer. The aim of this study was to analyse the association between IMTP variables, with common markers of athletic performance capability. METHODS: Eleven professional development soccer players (age: 20 ± 2 years, stature: 1.82 ± 0.10 m, mass: 76.4 ± 12.8 kg) performed IMTP, 5 m and 10 m accelerations, maximal sprint speed (MSS), countermovement jump (CMJ), and the 505 chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Conversely, a positive correlation emerged between lower limb power, as measured by the CMJ, and lower limb isometric strength, quantified through the IMTP), with a correlation coefficient of 0.57. These findings align with outcomes reported in previous studies after implementing CT programs (Mason et al, 2021;Liu et al, 2022;Qiao et al, 2022). For instance, Comfort and others, in their study with elite 17-year-old soccer players, identified a similarly strong negative correlation between maximal strength and 20-m sprint times, with a coefficient of −0.64 (Comfort et al, 2014).…”
Section: Correlations Between Changes In Physical Performance Variablessupporting
confidence: 89%
See 1 more Smart Citation
“…Conversely, a positive correlation emerged between lower limb power, as measured by the CMJ, and lower limb isometric strength, quantified through the IMTP), with a correlation coefficient of 0.57. These findings align with outcomes reported in previous studies after implementing CT programs (Mason et al, 2021;Liu et al, 2022;Qiao et al, 2022). For instance, Comfort and others, in their study with elite 17-year-old soccer players, identified a similarly strong negative correlation between maximal strength and 20-m sprint times, with a coefficient of −0.64 (Comfort et al, 2014).…”
Section: Correlations Between Changes In Physical Performance Variablessupporting
confidence: 89%
“…For instance, Comfort and others, in their study with elite 17-year-old soccer players, identified a similarly strong negative correlation between maximal strength and 20-m sprint times, with a coefficient of −0.64 (Comfort et al, 2014). Additionally, a substantial correlation between IMTP and CMJ was documented in another investigation, reinforcing the theory that augmentations in lower-body strength positively influence sprint performance and lower limb power (Mason et al, 2021). Therefore, the CT approach, which emphasizes high-load resistance training combined with plyometric exercises, is increasingly recognized as an effective strategy for enhancing sprint performance and the power of the lower limbs.…”
Section: Correlations Between Changes In Physical Performance Variablesmentioning
confidence: 65%
“…Maximum strength, as a basic strength ability, positively influences the performance of explosive strength [29]. Several studies have analyzed the relationships between maximum strength and sprint or jump performance in soccer [30][31][32][33][34][35][36], utilizing various methods including isometrics (r = |0.23-0.80|) [30,34,37,38], isokinetics (r = |0.22-0.48|) [34], and free-weight squats (r = |0.28-0.94|) [30][31][32]34,36]. The findings in previous studies suggest an influence of absolute (r = |0.02-0.94|) [30,32,34,36,[39][40][41][42][43] and relative strength (maximum strength performance divided by body weight [REL], r = |0.01-0.72|) [30,32,42,43] on various sprinting and jumping performances.…”
Section: Introductionmentioning
confidence: 99%
“…4 The IMTP is a useful exercise in rehabilitation because it has been correlated to athletic capabilities of strength, maximal sprint speed, countermovement jump, and change of direction tests. [33][34][35] Bench press as well as barbell military press were initiated at six weeks post-op due to the subject's previous experience and desired goals as well as the limited involvement of the bicep in these activities. Saeterbakken and colleagues 36 previously found that that flat bench press resulted in 48.3%-68.7% less bicep activity than incline bench position and that a narrow grip (biacromial distance) elicited lower bicep loads than a wide grip (50% more than biacromial distance).…”
Section: Case Descriptionmentioning
confidence: 99%